DEVELOPMENT OF STUDENT NEEDS ASSESSMENT GUIDELINES IN PLANNING GUIDANCE AND COUNSELING PROGRAMS - Romiaty; Apriatama, Dony; Pangestie, Esti Pan; Stevandy, Matias (EDUCATIONE, 2024)
The Coronavirus Disease 2019 (Covid-19) pandemic has necessitated the adaptation of daily life, including education, to coexist with the virus, commonly termed the "new normal." This study investigates the implementation of needs assessment activities for counseling programs in Palangka Raya City Public High School during the Covid-19 pandemic era. Interviews with key personnel reveal that while there is recognition of the importance of needs assessment, practical challenges hinder its effective execution. Guidance counselors often resort to using previous years' programs due to difficulties in data collection and analysis, resulting in counseling services that may not align with student needs. To address this, operational guidelines are proposed, emphasizing the utilization of technology for needs analysis activities. Expert and practitioner feedback underscores the importance of adapting assessment models to counselor capabilities and school contexts. Enhancing student-centered needs assessment practices is crucial for improving counseling program efficacy and supporting holistic student development.